Tutorial Mendeley Reference Manager untuk Menulis Karya Ilmiah bagi Guru-Guru SMP Negeri 2 Dumai - Alber Alber; Fauzul Etfita; Rijali Abdilla Zhikri; Pajriansyah Pajriansyah (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The flow of globalization, technological developments, and science requires teachers to be able to answer challenges by increasing self-competence. One of the competencies needed to deal with this is creativity in the form of scientific work. Having the ability to write scientific papers is one of the factors that can improve the professionalism of a teacher in addition to being able to make lesson plans, make teaching materials, learning media, and so on. However, based on observations there are still many teachers, especially at SMP N 2 Dumai, have not been able to understand how to write scientific papers properly and correctly, including how to cite and make references using computer application systems, so far teachers are still using the manual system. This problem is certainly very important to find a solution, because the demands in the world of scientific publications at this time, especially journals that have national and international accreditation, are required to use computer applications, one of which is the mendeley reference manager as a condition for acceptance (acceptable / anti-reject) in the journal target publication. . Therefore, this training is one of the efforts to improve the quality of teachers. The training is carried out using a classical and individual approach. Based on the results and discussion, it can be concluded that the Mendeley reference manager tutorial for writing scientific papers for teachers of SMP Negeri 2 Dumai can be categorized as successful and according to the set targets.